2017
DOI: 10.1080/20008198.2017.1298311
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged grief, depression, and posttraumatic stress in disaster-bereaved individuals: latent class analysis

Abstract: Background: Hundreds of individuals lost one or more significant others in the MH17 plane crash in 2014 in Ukraine. The current study is the first to explore subgroups of disaster-bereaved individuals based on presence of psychopathology clusters. This may inform the development of diagnostic instruments and tailored interventions. Objective: Aims of the current study were to examine (1) subgroups based on presence of prolonged grief disorder (PGD), major depressive disorder (MDD), and posttraumatic stress dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 53 publications
9
84
1
Order By: Relevance
“…Evidently, few individuals in this group reached the diagnostic criteria for depression, PTSD and PGD, 3%, 2% and 0%, respectively. This finding is consistent with previous research that demonstrates that some bereaved parents could still maintain general physical and psychological health and exhibit resilience in their recovery even after undergoing an extremely traumatic event (Djelantik et al, 2017; Lenferink et al, 2017; Spahni et al, 2015; Zhou et al, 2018). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Evidently, few individuals in this group reached the diagnostic criteria for depression, PTSD and PGD, 3%, 2% and 0%, respectively. This finding is consistent with previous research that demonstrates that some bereaved parents could still maintain general physical and psychological health and exhibit resilience in their recovery even after undergoing an extremely traumatic event (Djelantik et al, 2017; Lenferink et al, 2017; Spahni et al, 2015; Zhou et al, 2018). …”
Section: Discussionsupporting
confidence: 92%
“…Previous research reported that subgroups of bereaved people were distinguished by the dominance of particular symptom profiles (e.g. predominantly PGD and comorbid symptom clusters such as PGD/PTSD or PGD/PTSD/depression; Djelantik et al, 2017; Lenferink et al, 2017). The inclusion of post-traumatic growth instead of only negative symptoms could contribute to the profile of classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, strong grief reactions, post-traumatic stress disorder (PTSD), and developmental difficulties have been observed (Eth & Pynoos, 1994; Hardesty, Campbell, McFarlane, & Lewandowski, 2008; Harris-Hendriks, Black, & Kaplan, 2000), in line with reactions to other major traumatic loss reported in the broader literature (e.g. Boelen & Smid, 2017; Christ, Siegel, & Christ, 2002; Lenferink, de Keijser, Smid, Djelantik, & Boelen, 2017; Miller, 2009). While clinical experience suggests that a substantial number of children require long-term mental health and social services, little empirical evidence is available regarding the circumstances and outcomes of children bereaved by parental intimate partner homicide.…”
Section: Introductionmentioning
confidence: 73%
“…Most participants will be recruited during an on-going longitudinal survey study that started in May 2015 (Lenferink, de Keijser, Smid, Djelantik, & Boelen, 2017). In the first measurement occasion of this survey study, about one-year post-disaster, participants are asked whether they are interested in receiving information about a treatment study.…”
Section: Methodsmentioning
confidence: 99%